Functional properties of hydrocolloids extracted from alugbati (Basella rubra) in food model systems - Fernandez, Fiona Gaile L.
The leaves and stalks of alugbati were separated to determine which plant part would give the higher hydrocolloid yield. Extraction with water was done at varying suspension durations at 80ºC while precipitation was performed using technical grade ethanol. Alugbati stalks gave a higher yield at the optimal extraction time of 30 minutes. Hydrocolloid obtained from both plant parts was determined to have 92.66% DE and a viscosity of 4.70 cP at 2% (w/v) concentration. Incorporating the hydrocolloid in food model systems, it was revealed that processing at low and high temperatures and the addition of salt decreased the viscosity of the solution. Also, hydrocolloid solution was not able to form gels with the addition of sugar and acid. However, hydrocolloid was determined to be stable at pH 5 and can emulsify oil and water. With the results obtained, alugbati hydrocolloids may be incorporated in food, but further research is needed to determine other extraction methods to get a more pure hydrocolloid that may exhibit better functional properties. Research on the combination of alugbati with other hydrocolloids may also be explored to enhance its use in food.